Vật liệu compozit “xanh” từ nhựa polylactic axit và sợi nứa Việt Nam - Thuỷ, Nguyễn Thị; Chương, Bùi (Vietnam Journal of Chemistry, 2014)
Polylactic acid (PLA) is the first commodity polymer produced from annually renewable resources. Its degradation is caused by hydrolytic cleavage of the polymer backbone with or without enzymes. However, PLA is commontly termed as a biodegradation polymer. Schizostachyum funghomii McClure is also a biodegradable material. So polymer composite (PC) material based on PLA and fiber of Schizostachyum funghomii McClure is call green composite with mechanical properties depending remarkably on kind of fiber (untreated or treated fibers). Water absorption capacity of material was evaluated through weight gains while scanning electron microscope (SEM) was used to study the morphology of surface of sample after soaking in chemical or biological medium. Thermal degradation temperature of PC was slightly lower than that of pure PLA. The weight remaining of PLA in neat PLA or PC sample is a function of elapsing time while the weight remaining of PLA in both samples after soaking in biological medium decreased almost linearly with elapsing time. In all medium, the degradation of PLA in neat PLA was slower than that of in PC sample. Keywords: Green polymer composite, polylactic acid, Schizostachyum funghomii McClure.